2010
DOI: 10.1590/s1413-86702010000600001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of viruses associated with gastrointestinal infection in HIV-positive patients

Abstract: Background: Diarrhea is a major cause of morbidity and mortality among HIV-infected patients worldwide. Objective: We sought to determine the frequency of viral gastrointestinal infections among Brazilian HIV-infected patients with diarrhea. Methods: A collection of 90 fecal specimens from HIV-infected individuals with diarrhea, previously tested for the presence of bacteria and parasite was analyzed by polymerase chain reaction and sequence analysis for the presence of enteric viruses such as astrovirus, noro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Intestinal bacterial and parasitic infections are common in developing countries and responsible for most acute and chronic diarrhea cases amongst HIV/AIDS patients (Silva et al, 2010). Females were more affected (13.3%) than males (8.2%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal bacterial and parasitic infections are common in developing countries and responsible for most acute and chronic diarrhea cases amongst HIV/AIDS patients (Silva et al, 2010). Females were more affected (13.3%) than males (8.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its destructive effect on the immune system, HIV infection further exposes the individual to multiple opportunistic infections. From the beginning of the HIV pandemics in the 1980s, gastrointestinal diseases have been demonstrated to be a major problem in patients with HIV and AIDS, and diarrhea is reported in up to 60% of patients with AIDS in developed countries and up to 90% in developing countries (Siddiqui et al, 2007;Silva et al, 2010). Recent studies by Bradshaw et al, (2005) have indicated that HIV/AIDS is the leading cause of premature mortality for all provinces in South Africa and mortality due to pretransitional causes, such as diarrhea, is more pronounced in the poorer and more rural provinces.…”
Section: Introductionmentioning
confidence: 99%